Effects of long-term application of organic fertilizer on improving organic matter content and retarding acidity in red soil from China - Wang, Hanxi; Xu, Jianling; Liu, Xuejun; Zhang, Di; Li, Longwei; Li, Wei; Sheng, Lianxi (Soil & tillage research, 2019)
•Soil pH decreased by 0.07 annually after 20 years of applying NPK fertilizers.•Long-term application of organic fertilizer increased soil SOC content.•Organic fertilizer resulted in higher grain yield than NPK alone.•Applying organic fertilizer alone prevents soil acidification. Long-term fertilization causes declines in soil quality and crop yield, hindering current agricultural development. This paper is about the effect of long-term fertilization (20 years) in Hunan’s Qiyang County. It was found that chemical nitrogen, phosphorus, and potassium (NPK) fertilizer lowered soil pH by an annual average of 0.07, while organic fertilizer increased soil pH by about 0.04. Furthermore, organic fertilizer and chemical fertilizer both increased total soil organic carbon (SOC). Long-term chemical NPK and organic fertilizer increased straw and grain yield of wheat and maize to a greater extent than did other fertilization methods. Thus, our results suggest that mixing organic fertilizer with chemical NPK fertilizer should prevent soil acidification and elevate crop yield.